The application of Google Earth Engine platform to assess the erosion - accretion processes of the estuary and coastal areas of Tra Khuc river, Quang Ngai province, Vietnam - Dao, Dinh Cham; Nguyen, Van Hong; Nguyen , Ngoc Thang; Nguyen , Thanh Binh (Vietnam Journal of Marine Science and Technology, 2023)
Along with storms, tides,... human activities have also affected the erosion - accretion process of the coast and estuaries. When global climate change increases the risk of shoreline change in a negative manner, monitoring and quick assessment of this change is of great importance. Google has developed a cloud computing platform, called Google Earth Engine, to effectively address the challenges of big data analysis. This study aims at exploiting and processing multi-temporal satellite images of the Google Earth Engine platform (GEE), combined with topographic data since 1965 to monitor changes in estuary and shoreline of the coastal area of Cua Dai, Tra Khuc river, Quang Nam province during a period of 1965–2021. The analysis results show shoreline changes and hot spots of erosion and landslides along the coast, on both sides of Cua Dai river. After 56 years, the process of erosion - accretion in the river occurs strongly. The eroded riverbanks are located mainly along alluvial plains away from residential areas. Meanwhile, the coast along Cua Dai estuary changes in favor of accretion. However, in recent years, local erosion still occurs in some coastal areas with a length of 0.7–1.2 km in the territory of Pho An - Tan My villages (Nghia An commune). The study shows the potential for directly exploiting and processing large amounts of free satellite image on the GEE for resource monitoring and management applications.